INTEGRATED MARKETING COMMUNICATION ON THE EVALUATION OF POSITIVE BRAND EXTENSION IN BANKING INDUSTRIES A study of Brizzi Product in Malang City - Prabowo, Ardian Wahyu; Yulianti, Ida (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to examine the influence of the four Integrated Marketing Communication that consist of Advertising, Sales Promotion, Events and Experiences, Personal Selling on the evaluation on Positive Brand Extension either partially and simultaneously on Brizzi consumers in Malang city. The type of research is explanatory research. This research was conducted in Malang city. There are 100 questionnaires distributed to every consumer who has used or brought Brizzi. The sampling technique was purposive sampling and the research instruments were tested using the Validity Test and Realibility Test. The data analysis testing used Multiple Regression Analysis. The hypothesis testing used was T-Test and F-Test. The results of the data analysis showed that all of variables in Integrated Marketing Communication has influence toward among four variables of Integrated Marketing Communication.Advertising   variable   has   dominant   influence   toward   Positive   Brand Extension partially and simultaneously. The results from this study can be applied in marketing strategy of banking industries and all interested parties for retaining and maximizing Integrated Marketing Communications to get a positive extension effects in the eyes of consumers and potential consumers.   Keywords: Integrated Marketing Communications, Positive Brand Extension, Brizzi, BRI